BEGAM, a new apparatus for the identification of β emitter contaminants in radiopharmaceuticals - Perri, Marco; Nannini, Adriana; Casini, Giovanni; Piantelli, Silvia; Nicastro, Giulia; Passeri, Alessandro; Saletti, Paola (HNPS Advances in Nuclear Physics, 2025)
The BEGAM project aims at developing a portable detector capable of performing γ/β coincidence and anti-coincidence measurements to estimate the presence of long-lived β-contaminants in radiopharmaceutical solutions. A preliminary prototype of the apparatus is under construction. It is composed of four sectors of Caesium Iodide (CsI) scintillators surrounding a cylindrical plastic scintillator. The scintillation readout is performed via silicon photomultiplier (SiPM) and after some preamplification the signals are sent to a commercial digitizer. Geant4 simulations of the detector’s response have been developed and validated using gamma and electron sources. Preliminary γ/β coincidence measurements from a 207Bi source have been performed. Near-future plans include testing the BEGAM detector to estimate the activity of 99Mo contaminants in 99mTc solutions.